2002
DOI: 10.1046/j.1439-0450.2002.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of the Full‐Length Cloned DNA of a Chicken Anaemia Virus (CAV) Strain from Bangladesh: Evidence for Genetic Grouping of CAV Strains Based on the Deduced VP1 Amino Acid Sequences

Abstract: Chicken anaemia virus (CAV) was detected in the bursa of Fabricius of a 4-week-old chicken obtained from an outbreak of acute infectious bursal disease in Bangladesh. Repeated attempts to grow this virus in MDCC-MSB1 cells were not successful. A full-length PCR amplicon of the genome of this strain, designated as BD-3 CAV, was cloned and sequenced. The complete nucleotide sequence and the deduced amino acid sequence were compared with those of 12 other CAV strains. The genetic analysis of the amino acid sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 39 publications
2
44
0
3
Order By: Relevance
“…Three genetically distinct genotypes (I, II, and III) have been recognized in classical CAV based on the phylogenetic analysis of the VP1 gene (Craig et al, 2009;Ducatez et al, 2008;Ducatez et al, 2006;Islam et al, 2002;Kim et al, 2010;Snoeck et al, 2012). Genotypes II and III are reported to be distributed worldwide, whereas genotype I is composed solely of isolates from Australia (Kim et al, 2010).…”
Section: Advances In Animal and Veterinary Sciences May 2016 | Volumementioning
confidence: 99%
“…Three genetically distinct genotypes (I, II, and III) have been recognized in classical CAV based on the phylogenetic analysis of the VP1 gene (Craig et al, 2009;Ducatez et al, 2008;Ducatez et al, 2006;Islam et al, 2002;Kim et al, 2010;Snoeck et al, 2012). Genotypes II and III are reported to be distributed worldwide, whereas genotype I is composed solely of isolates from Australia (Kim et al, 2010).…”
Section: Advances In Animal and Veterinary Sciences May 2016 | Volumementioning
confidence: 99%
“…A detecção do DNA do CAV a partir de cultivos celulares, como proposto previamente (Todd et al 1992, Imai et al 1998, é pouco prática na rotina diagnóstica, uma vez que são necessários dias para a multiplicação do vírus, o que torna o diagnóstico mais demorado e oneroso. Além disso, algumas amostras não replicam em cultivos celulares (Islam et al 2002), podendo gerar resultados falsos negativos.…”
Section: Discussão E Conclusões Discussão E Conclusões Discussão E Counclassified
“…Além de o isolamento viral apresentar baixa sensibilidade (Cardona et al 2000), diferenças genéticas interferem na replicação do vírus (Renshaw et al 1996) o que impossibilita o isolamento de algumas cepas (Islam et al 2002). Já os testes sorológicos indicam uma exposição prévia ao vírus e não uma infecção presente (Schat 2003).…”
Section: Introdução Introdução Introdução Introdução Introduçãounclassified
“…MSB1 culture eventually exhibits a cytopathic effect (CPE) characterized by the appearance of enlarged cells, cell destruction, alkaline medium and loss of the ability to grow [2,6,11,25]. Although most CAV strains could be propagated on MSB1, recent isolates that lack the ability to infect and propagate on MSB1 have been reported in America [2,15,20], Bangladesh [8] and Brazil [14]. Moreover, some researchers have found that isolation of CAV using MSB1 may require from 10 to 16 passages [21] before the CPE becomes evident.…”
mentioning
confidence: 99%
“…Although MSB1 has been widely used for CAV isolation and propagation, some biological problems have been reported such as no support for the propagation of some recently isolated strains, i.e., 59058 and TR20 [20], BD3 [8] and BR47/90 [14]. MSB1 may lose its ability to support CAV propagation after a longer passage [22].…”
mentioning
confidence: 99%